Digital Marketing, Attractions, and Services as Drivers of Tourist Satisfaction and Loyalty: Evidence from Mount Dempo, South Sumatra - Elvera Elvera; Diah Natalisa; Sastra Mico; Nisa Rahmaniyah Utami (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study examines the effects of digital marketing, tourist attractions, and tourism services on tourist satisfaction, loyalty, and word of mouth, with brand trust as a mediating variable. A survey of 255 visitors to Mount Dempo, South Sumatra, was conducted using a quantitative approach and analyzed with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results indicate that digital marketing, attractions, and services significantly influence brand trust and satisfaction, which in turn drive loyalty and positive word of mouth. Furthermore, brand trust mediates the relationship between the three exogenous variables and the outcome variables, highlighting its strategic role in building long-term tourist loyalty. These findings support the Expectancy–Disconfirmation Theory, emphasizing the importance of aligning digital narratives with on-site experiences. The study contributes to both theory and practice by demonstrating the integrated role of digital promotion, attraction development, and service quality in fostering trust-based sustainable tourism. Keywords: Digital marketing, tourist attractions, tourism services, brand trust, satisfaction, loyalty, word of mouth, SEM-PLS